Effect of Self Efficacy, Training, Motivation, and Competence on Organizational Commitment with Employee Performance as Intervening Variables at PT Bina Utama Sakti - Tukfa Qurotalain; Sriyono Sriyono; Hadiah Fitriyah (MIX: JURNAL ILMIAH MANAJEMEN, 2022)
The problem on this research is that there may be a lower overall performance at PT Inkasa Jaya Aluminium which is due to the shortage of advantageous factors which include self-efficacy, training, motivation, and competence of PT Bina Utama Sakti personnel whose work at PT Inkasa Jaya Aluminium influences the decline in organizational dedication and worker overall performance.Objective: To investigate the impact of self-efficacy, training, motivation, and competence on organizational dedication with worker overall performance as an intervening variable.Methodology: Based on the approach of facts collection, the researcher used quantitative studies techniques with surveys. The number of samples in this study was 100 employees of the production division at PT Bina Utama Sakti. The data analysis method in this study is using SEM analysis with mediating effects using the SmartPLS3 application to determine P-values and Path Coefficient Test as hypothesis testing.Finding: The effects that are looked at are: Self-efficacy, motivation, and competence that don’t have any great and insignificant impact on organizational dedication; Training has a great and huge impact on organizational dedication; Self-efficacy, training, and motivation don’t have any great and insignificant impact on worker overall performance; Competence has a great and huge impact on worker overall performance; Employee overall performance has a great and huge impact on organizational dedication; Self-efficacy, training, motivation, and competence can't have an impact on organizational dedication via worker overall performanceConclusion: To optimize performance, the company should make a special policy to be able to further improve the self-efficacy, training, motivation, and competence of their employees to maximize their performance in increasing the company's success in achieving its goals.Keywords: Competence;Employee Performance; Motivation; Organizational Commitment; Self-Efficacy